Stratégies d’accommodation dans l’émission de débat politique Question Time (BBC1) : le cas de l’interro-négative - Pauline Levillain (Anglophonia)
This paper endeavours to open new perspectives on the contribution of negative interrogatives to the accommodation strategies used by the speaker in the interactions taking place in the TV debate Question Time (a corpus collected by Laurent Rouveyrol at the University of Nice, France). It shows that the negative interrogative clause is not the negative counterpart of the usual, positive, interrogative clause by shedding light not only on the argumentative value of the message conveyed, namely the point of view expressed by the clause, but also on the indirect speech act it enables its speaker to perform (Searle 1979). After analysing the accommodation strategies put in place in a context of natural conversation in American English (Levillain 2017b), this study goes further into the accommodation strategies related to the specificity of a TV debate corpus.